Impact of Diagnosis-Related Groups on Inpatient Quality of Health Care: A Systematic Review and Meta-Analysis - Ya-jing Chen MSc; Xin-yu Zhang PhD; Jia-qi Yan MSc; Xue-Tang MSc; Meng-cen Qian PhD; Xiao-hua Ying PhD (SAGE Publishing, 2023)
The aim of this meta-analysis was to comprehensively evaluate the effectiveness of Diagnosis-related group (DRG) based payment on inpatient quality of care. A comprehensive literature search was conducted in PubMed, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science from their inception to December 30, 2022. Included studies reported associations between DRGs-based payment and length of stay (LOS), re-admission within 30 days and mortality. Two reviewers screened the studies independently, extracted data of interest and assessed the risk of bias of eligible studies. Stata 13.0 was used in the meta-analysis. A total of 29 studies with 36 214 219 enrolled patients were analyzed. Meta-analysis showed that DRG-based payment was effective in LOS decrease (pooled effect: SMD = −0.25, 95% CI = −0.37 to −0.12, Z  = 3.81, P  < .001), but showed no significant overall effect in re-admission within 30 days (RR = 0.79, 95% CI = 0.62-1.01, Z  = 1.89, P  = .058) and mortality (RR = 0.91, 95% CI = 0.72-1.15, Z  = 0.82, P  = .411). DRG-based payment demonstrated statistically significant superiority over cost-based payment in terms of LOS reduction. However, owing to limitations in the quantity and quality of the included studies, an adequately powered study is necessary to consolidate these findings.